Co-printing of vertical axis aligned micron-scaled filaments via simultaneous dual needle electrohydrodynamic printing. (July 2018) - Wang, Baolin; Wu, Shuting; Ahmad, Zeeshan; Li, Jing-song; Chang, Ming-Wei
Graphical abstract: Highlights: Multi-needle co-printing of vertically aligned fibers is shown. Biocompatible multi-material composites generated in one-step. Sacrificial PVP fibers can be used to generate voids in-situ. Drug release is controlled based on fiber patterning and geometry. An external magnetic trigger assists drug release control. Abstract: In this study dual-needle electrohydrodynamic co-printing (DN-EHDCP) was developed to fabricate unique micron-scaled architectures based on multi-material fibrous (filamentous) morphologies. Two stainless steel needles (contributing towards dual needle design) were used to simultaneously co-print poly(ɛ-caprolactone) (PCL) and polyvinylpyrrolidone (PVP) polymers (using solvent based formulations including Fe3 O4 nanoparticles and active pharmaceutical ingredient (API). Differences in polymer hydrophobicity and dissolution rate were used to modulate drug release (tetracycline hydrochloride, TE-HCL) from various co-printed configurations. Optical, scanning electron and fluorescent microscopy confirmed precision alignment and vertical stacking of both PVP and PCL printed filaments. Process parameters were found to strongly influence co-print construct diameter. Fourier Transform Infrared (FTIR) spectroscopy confirmed spatial locations of both PVP and PCL filaments. TE-HCL release from co-printed formulations exhibited two phases; rapid and sustained. In vitro biological assay (using L929 cell lines) demonstrated construct biocompatibility. However, selective integration (spatial and quantity) of sacrificial PVP fibers (after rapid dissolution) provided a method of in situ void engineering for enhanced interfacial interaction for remaining PCL structures. The present study shows the development and use of simultaneously co-printed filaments in the vertical axis with potential to control drug release through alignment of individual filaments and material type. Furthermore, the use of composite matrix under an external stimulus is also demonstrated indicating multiple approaches to modulate API release.